Ammoniacal Nitrogen Removal From Landfill Leachate By Heat Activated Zeolite - Yap, Wei Keat (Universiti Sains Malaysia, 2019)
This study was undertaken to determine the performance of raw zeolite and heat activated zeolite to treat the landfill leachate from Alor Pongsu landfill, as a case study site. The landfill leachate was collected for three times between 19th February and 25th March 2019 and then was characterized for the main leachate parameters. The raw zeolite was characterized by the X-ray diffraction, X-ray fluorescence, Scanning electron microscopy and Brunauer-Emmett-Teller instrument, later sieved to size 2-4mm and was used as the adsorbent. Batch studies were undertaken at different adsorbent dosages and pH values. The Langmuir and Freundlich isotherm parameters were also determined. The performance of raw zeolite was compared with the activated zeolite, heated at 150°C, 200°C and 250°C. Results indicated that the average leachate parameters monitored were pH 8.09, temperature 25.5°C, ammoniacal nitrogen 1080mg/L, dissolved oxygen 1.0mg/L, chemical oxygen demand 3743mg/L, apparent colour 16250PtCo, true colour 13077PtCo, zeta potential -21.0mV and total suspended solid 388mg/L. Based on the X-ray diffraction and X-ray fluorescence analysis, the zeolite was identified as quartz. Based on the batch results, the activated zeolite heated at 150°C showed better performance. Using raw zeolite, at an optimum dosage of 10 g, the ammoniacal nitrogen removal was 55.8% at an optimum pH 7. However, at an optimum pH 4, the removal for COD and the true color was 24.3% and 73.8%, respectively, at the same dosage (10 g). For activated zeolite heated at 150°C, at optimum dosage of 10 g, the ammoniacal nitrogen removal was 67.0 % at an optimum pH 8. However, at an optimum pH 4, the removal for COD was 46.3%, and the reduction of true color was 91.4% at an optimum pH 5; both at the same dosage (10 g). The improvements in the removal performance after heat treatment were 11.2%, 22%, and 17.5%, respectively, for ammoniacal nitrogen, COD and true colour. The cation exchange capacity of the zeolite is also expected to contribute to the removal of the pollutants. The adsorption isotherm analysis revealed that both Langmuir and Freundlich isotherms fitted well with the experimental data. However, the Freundlich isotherm model is more suitable than Langmuir isotherm for evaluating the adsorption equilibrium required for COD, NH3-N and true colour as verified by the high R2 values.